Interaction structures in local innovation systems - Uwe Cantner; Holger Graf (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
The flow of knowledge through interaction between innovative actors is central to the systemic view of innovation. We review the literature on interaction and innovator networks with a focus on regional aspects. To illustrate the relevance of these relations, we apply social network analysis methods to describe the evolution of the innovator network of Jena, Germany in the period from 1995 to 2001. During this period, the network is characterised by growth in the number of patents, actors and relations, with central positions of public research. The evolution is directed towards an increasing focus on core competencies of the network.
Keywords: O31; L14; R11; 330; Innovator networks; innovation system; R&D cooperation; mobility; Innovation; Business Network; Forschungskooperation; Soziales Netzwerk; Region; Evolutionsökonomik; Kernkompetenz; Deutschland; Jena (Region)